EVALUASI RISK MANAGEMENT BAHAYA PENCEMARAN GAS MUDAH TERBAKAR DAN BERACUN MELALUI IMPLEMNTASI SISTIM KESEHATAN DAN KESELAMATAN KERJA (K3) STUDI KASUS: PT XYZ OIL GAS COMPANY - Fauzi Khair; Rahmat Sabani (KAIZEN : Management Systems & Industrial Engineering Journal, 2022)
The company's activities engaged in the oil and gas exploration and processing have many potential risks of work accidents in their business processes. Therefore, management and evaluation of risk management need to be carried out related to work activities. Especially those that have close proximity to methane gas as a combustible gas, and H2S gas as a toxic gas. The research was conducted in five divisions/departments in QATAR Oil Gas Company such as instrument, electrical, civil, mechanical, production and civil divisions. Each activity has a different level of risk, so it is required to measure the priority level of each. Based on the results, it was found that the production division has the most risk sources compared to other divisions as many as 17 sources and has the highest priority level. After the risk sources are identified and analyzed, a risk management proposal is designed by adjusting the type of activity and the risk. Management and application of personal protective equipment (PPE), SOP work procedures and fire extinguishers are one of the risk management proposals that must be adhered to as part of risk management.